Comrade loves of the samurai - Ihara, Saikaku (Tuttle, 1972)
In old Japan, sexual love among the samurai was permissible, and often matured into lifelong companionships. Comrade Loves of the Samurai touches the subject of both normal and abnormal love with honesty and tenderness.